Exploring healthcare provider retention in a rural and frontier community in Northern Idaho - Jonathan D. Moore; Allie M. Lords; Madeline P. Casanova; Ashley J. Reeves; Ann Lima; Cody Wilkinson; Sarah M. Deming; Russell T. Baker (BMC, 2024)
Abstract Background A shortage of healthcare providers, particularly in primary care and mental health, exists in the predominately rural state of Idaho. There are also barriers to retaining healthcare providers to work in rural and remote communities. Limited research using U.S. samples has explored factors that may affect the retention of healthcare providers in rural areas. Additionally, due to differences between communities, it is important to conduct community-level investigations to better understand how these factors may affect retention in rural areas. Therefore, the purpose of this study was to explore factors affecting healthcare provider retention in a rural community in Northern Idaho. Methods A modified version of the Nursing Community Apgar Questionnaire (NCAQ) was completed by 30 healthcare providers in a rural and frontier community in Northern Idaho to assess factors influencing healthcare provider retention. Factors were classified into classes including geographic, economic, scope of practice, medical support, and facility and community support classes. Retention factors were assessed on their perceived importance to retention as well as whether they were perceived as an advantage or challenge to retention based on Likert scales. A "Community Apgar" score was also created by combining the importance and advantage/challenge factors. Results Overall, items in the medical support group had the highest importance of any other class and included factors such as nursing workforce. Additionally, the facility and community support class, which included factors such as televideo support, was rated the highest advantage class and had the highest Apgar score, indicating it contained the factor that healthcare providers identified as the most important advantage (i.e., medical reference resources). Conclusion Our study identified multiple factors that healthcare providers deemed as important advantages or disadvantages to retaining healthcare providers in rural areas. Overall, facility and community support factors were found to have the highest advantage in the retention of rural providers. Rural healthcare organizations looking to increase healthcare provider retention should target retention efforts towards these factors. Additional research should also be conducted on other rural samples across the U.S. to make comparisons of findings.